The patterns of dynamic changes in blood toxicant levels, prognosis, and regression in a case of occupational chlorfenapyr exposure - Liu, Jianjian; Shan, Zhaozhao; Wang, Chen; Jian, Xiangdong; Kan, Baotian; Ren, Yingli (Frontiers in Toxicology, 2025)
ObjectiveIn July 2024, cases of chlorfenapyr poisoning occurred consecutively among workers in a chlorfenapyr production plant in Shandong Province. This study aimed to analyze the clinical characteristics of this event and discuss the significance of toxicant testing and imaging examinations in guiding clinical practice.MethodsWe retrospectively analyzed the clinical data of four patients with occupational chlorfenapyr poisoning.ResultsAll four patients worked in the same factory before admission; three worked in the same workshop, while one worked in the product inspection department. Patients three and four had no obvious clinical manifestations, whereas patients one and two primarily presented with hyperhidrosis, fever, and neurological symptoms. Laboratory tests revealed abnormalities in blood counts, liver and kidney function indicators, and cardiac enzyme profiles in some patients. Magnetic resonance imaging revealed varying degrees of abnormal signal changes in the brain and spinal cord in Patients 1, 2, and 3. After comprehensive treatment with blood purification, organ protection, and symptomatic treatment, chlorfenapyr blood concentrations in patients 1, 2, and 3 decreased. Patients one and three were discharged on the 30th and 14th days of admission, respectively, while patient 2, whose condition worsened, died on the 11th day of treatment after unsuccessful resuscitation.ConclusionPatients with occupational chlorfenapyr poisoning may have no obvious clinical symptoms or may present with excessive sweating and fatigue in the early stages, unlike patients who have ingested chlorfenapyr orally. Therefore, early detection and imaging examinations are crucial for an accurate diagnosis.